KISS and tell - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 2001)
A key motto for communicators is 'Keep It Simple, Stupid!' or KISS in short. Sometimes though, even information specialists cannot speak clearly, and they end up transmitting convoluted and confused messages. This is lazy, since it often takes a lot...